Expression characteristics of proteins of IGF-1R, p-Akt, and survivin in papillary thyroid carcinoma patients with type 2 diabetes mellitus. Issue 12 (March 2017) - Yan, Yuerong; Hu, Fengqiu; Wu, Weilu; Ma, Ruiting; Huang, Hui
Abstract : Abstract: Type 2 diabetes mellitus (T2DM) is related to increased risk of papillary thyroid carcinoma (PTC). Insulin-like growth factor-1 receptor (IGF-1R) is increased in patients with T2DM. The increased IGF-1R may be responsible for the development of PTC. In this study, we investigated the expression of phosphorylation of Akt (p-Akt)/survivin pathway activated by IGF-1R in PTC subjects with and without diabetes. Clinicopathological data of 20 PTC patients with T2DM were retrospectively analyzed and compared with those of 21 PTC subjects without diabetes. Meanwhile, IGF-1R, p-Akt, and survivin expressions of PTC tissues were detected by immunohistochemical staining. The immunohistochemical results found that the expression level of IGF-1R was significantly higher in diabetic PTC patients than that in nondiabetic PTC patients ( P  < 0.05). However, no significant differences of p-Akt and survivin expression were found between PTC patients with T2DM and PTC patients without T2DM. In addition, among 20 PTC patients with T2DM, subgroup analysis showed that the ratio of tumor size >10 mm was significantly higher in IGF-1R moderate to strong expression group than that in IGF-1R negative to weak expression group ( P  < 0.05). IGF-1R expression level was higher in PTC patients with T2DM, and the increased IGF-1R expression was associated with lager tumor size. IGF-1R may play an important role in carcinogenesis and tumor growth in PTC patients with T2DM.